Pengaruh Pengendalian Internal Terhadap Pengelolaan Dana Zakat Pada BAZNAS Di Provinsi Gorontalo - Rily Pilomonu; Niswatin Niswatin; La Ode Rasuli (Jambura Accounting Review, 2021)
The research was aimed at finding out the influence of internal control on zakat funds management at the National Zakat Board (BAZNAS) in Gorontalo Province. The method employed in this research was a quantitative method. The population of this research was the whole of employees at the National Zakat Board in Gorontalo Province, which amounted to 91 employees. In addition, the sampling technique used was saturated sampling, where the numbers of samples as much as 30 people. The technique of data collection applied simple linier regression analysis. The finding showed that the internal factor positively influenced zakat funds management at the National Zakat Board (BAZNAS) in Gorontalo Provinces. The value of the coefficient of determination (R2) was 36,3%.